The Pakpak Ethnic Menerbeb Tradition: a Semiotic Study - Padang, Trihamdani (L'Geneus : The Journal Language Generations of Intellectual Society, 2019)
The problem in this research is how the form, function and meaning of the Pakpak ethnic grouping tradition will be studied in a semiotic manner, along with explaining the views of the Pakpak ethnic community on the Pakpak ethnic grouping tradition. Menerbeb is one part of a cultural tradition that is owned by the Pakpak ethnic group. This study aims to determine the function and meaning of cultural symbols, which are studied with the semiotic science contained in the Pakpak tradition and to find out the concept of thought and views of the Pakpak community on the function and food itself. The stages of implementing the Menerbeb tradition are structured, the author also explores the cultural values ??in it. The research method used by the author in analyzing this problem in the traditional research of menerbeb is descriptive method with field research techniques. This research uses semiotic theory which examines the science of signs with a combination of function theory and meaning theory of the research object.